PREVALENCE OF MENTAL DISORDERS IN SELECTED RURAL AND URBAN COMMUNITY - B Devaki; G. L. Hariskrishna; Jeeva Sebastian; K.G. Paul Prabhu; Rajeshwari Siva; Vathsala Sadan (Indian Journal of Psychiatric Nursing)
The purpose of this study was to identify the prevalence of psychiatric morbidity in selected urban and rural area of Vellore. A descriptive design was used to conduct the study. A population of 452 from urban and 324 from rural area were surveyed. A mental health screening tool was prepared by the investigators which had ten components, each of which has certain subsets that describe the nature of the problem under study. The data were analyzed by descriptive statistics. 8% in urban and 12 % in rural area are having mental health problems and among which 64.9% of urban subjects are having sleep disturbances and 37.8% with mood disturbances. Nearly half (47.4%) of rural subjects are having sleep disturbances and 34.2% with substance use disorders. The prevalence reported in epidemiological surveys can be considered lower estimates rather than accurate reflections of true prevalence in the population. Researchers have focused on broad non-specific, non-modifiable risk factors, such as age, gender and social class. Future research can be focused on the general population, longitudinal (prospective), multi-centre, co-morbid studies, assessment of disability and its functioning, family burden and quality of life studies involving a clinical service providing approach.